Does Evaluation Change Teacher Effort and Performance? Quasi-experimental Evidence from a Policy of Retesting Students - Aucejo, Esteban; Romano, Teresa; Taylor, Eric S. (The Review of Economics and Statistics, 2022)
We document measurable, lasting gains in student achievement caused by a change in teachers' evaluation incentives. A short-lived rule created a discontinuity in teachers' incentives when allocating effort across their assigned students: students who failed an initial end-of-year test were retested a few weeks later, and then only the higher of the two scores was used when calculating the teacher's evaluation score. One year later, long after the discontinuity in incentives had ended, retested students scored 0.03σ higher than nonretested students. Otherwise identical students were treated differently by teachers because of evaluation incentives, despite arguably equal returns to teacher effort.